Design and Building of A Portable Spirometer Based on Arduino Uno - Mohammad Rofi'i; Yanto, Feri (KH. A. Wahab Hasbullah University, 2023)
A spirometer is a medical instrument that functions to measure the capacity and volume of human lungs during expiration. This research is important because pulmonary function examination is an objective method of assessing changes in a person's lung function or suspected lung disorders, and assessing the type of treatment to be performed. In this study, a portable spirometer instrument was designed, which is a tool to measure the strength of the breath used to measure the amount of air volume that can be exhaled after maximum inspiration commonly called FVC (Forced Vital Capacity), VC (Vital Capacity), and the amount of air volume at the first second that can be expelled after maximum inspiration or commonly called FEV1 (Forced Expiratory Volume 1 second). This tool is designed using the MPX5500DP Air Pressure Sensor, which is an air pressure sensor to detect the pressure and airflow exhaled by the respondent through the mouthpiece pipe. There are 3 operating modes, namely, a test mode for measuring 3 parameters (VC, FVC, FEV1). Tool testing was carried out by comparing it with a standard tool that has been calibrated and measured using a calibration syringe. The results obtained were the percentage of accuracy or accuracy of measurement when measurements were made with a 3-litre Calibration Syringe of 98.1%, and the percentage of errors or reading errors when compared with a tool in the hospital or the market by 2.5%. The percentage error value is still within the tolerance limit of ±10%. From these results, it can be concluded that this tool can work well and can be used in pulmonary function examination.